Effect of Work Discipline on employee performance in the Office of Public Appraisal Services Herly, Ariawan and Partners - Eni Puji Astuti; Nur Amalah (Universitas Negeri Makassar, 2020)
A company is required to have a disciplined view and attitude to increase employee productivity, work discipline is the most important human resource management function and is closely related to the management of resources for a company. The purpose of this study was to determine the work discipline at the Public Appraisal Service Office Herly Ariawan and Partners, to determine the performance of employees at the Public Appraisal Service Office Herly Ariawan and Partners, to determine the work discipline on employee performance at the Public Appraisal Service Office Herly Ariawan and Partners. The research method used is quantitative associative. The data was obtained by distributing questionnaires using a saturated sample to 30 employees at the Public Appraisal Services Office Herly Ariawan and Partners. Analysis of the data used is a simple linear regression equation, simple correlation, coefficient of determination, and significance test. The population is 30 respondents with a sample of 30 respondents. There is a positive influence, between Work Discipline on Employee Performance at the Office of Public Appraisal Services Herly Ariawan and Partners based on hypothesis testing using t test that tcount> ttable or 2,053> 1,701 then show significant results. Or in other words, H0 is rejected and Ha is accepted. So it can be concluded that there is a significant influence between Work Discipline on Employee Performance at the Office of Public Appraisal Services Herly Ariawan and Partners.